In Vitro Antibacterial Evaluation of Terminalia chebula as an Alternative of Antibiotics against Bovine Subclinical Mastitis. Issue 2 (3rd April 2019) - Kher, Mukesh N.; Sheth, Navin R.; Bhatt, Vaibhav D.
ABSTRACT: The extent of subclinical mastitis in three breeds of cattle, Kankrej, Gir, and Crossbred, was performed at cattle farms in Anand town of Gujarat State, India. The prevalence of subclinical mastitis in crossbred cattle was higher compared to local breed of cattle. Causative agents identified using 16S rDNA polymerase chain reaction (PCR)-based molecular method were Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Bacillus megaterium. In vitro antibacterial activity of ethyl acetate extract of plant Terminalia chebula (Combretaceae) was checked by agar well diffusion method against four isolated and molecularly identified microorganisms. Ethyl acetate extract shows antimicrobial activity with varying magnitudes against all identified isolates. Among the three different concentrations, 500 µg/mL conc. of extract is as effective as that of standard amoxicillin. In vitro results support the use of plant extract from T. chebula as an alternative to antibiotics therapy against bovine subclinical mastitis.